Handbook of research on environmental and human health impacts of plastic pollution - Wani, Khursheed Ahmad; Ariana, Lutfah; Zuber, S. M., 1970- (Advances in environmental engineering and green technologies (AEEGT) book series., 2020)
Due to the non-biodegradability of plastic substances, coupled with poor waste management practices, plastic pollution has become a major environmental issue within the past decade. However, the negative effects of plastic pollution are rarely opposed, or the solutions proposed are costly or still damaging to the environment. New strategies must be undertaken to prevent irreparable environmental damage from disposable plastic products while maintaining and maximizing the benefits of plastics in specialized cases, such as medicine and public health.